Eighteen-month update on the movements and social organization of a population of black rhinos introduced to a new area by ‘same day’ free release translocation in Kenya - Felix Patton; Petra Campbell (Pachyderm)
Details of the free-release translocation of 27 black rhinos into a new area of the Ol Pejeta Conservancy in the Laikipia area of central Kenya were presented in Patton et al. (2010). The results for the first six months after release suggested that all the rhinos bar one had settled in their new environment. Research, as described below, was continued for a further 12 months to determine how the population developed as the individuals became more used to their new environment.